Ridgeline - Punke, Michael (New York Springer, 2014)
"In December 1866, tensions were rising in Wyoming, between the Native American tribes who had lived on the land for generations and the settlers who would destroy their home. Crazy Horse and his fellow Lakota hunters had been watching for months as Colonel Carrington and his army set up camp on one of the most crucial swaths of hunting ground in hundreds of miles, and began to build forts. More disconcertingly, the settlers had brought women and children, which meant they planned to stay. As the Lakota and neighboring tribes set forth with repeated attacks to discourage the settlers, Captain William J. Fetterman, anxious and arrogant, claimed that he could take offense and rid the area of Native American people with only a small army of 80 men. And he would--unless Crazy Horse could find a way to lure the army to their doom. A story of protection and betrayal, of courage, wit, and perseverance against unfathomable odds, Ridgeline grapples with essential questions about who owns land: those who are born on it, or those who would kill to claim it"--
Keywords: Lakota Indians